Fas Ligand DNA Enhances a Vaccination Effect by Coadministered DNA Encoding a Tumor Antigen through Augmenting Production of Antibody against the Tumor Antigen - Boya Zhong; Guangyu Ma; Ayako Sato; Osamu Shimozato; Hongdan Liu; Quanhai Li; Masato Shingyoji; Yuji Tada; Koichiro Tatsumi; Hideaki Shimada; Kenzo Hiroshima; Masatoshi Tagawa (Journal of Immunology Research)
Interaction of Fas and Fas ligand (FasL) plays an important role in the regulation of immune responses by inducing apoptosis of activated cells; however, a possible role of FasL in DNA vaccination has not been well understood. We examined whether administration of DNA encoding FasL gene enhanced antitumor effects in mice that were vaccinated with DNA expressing a putative tumor antigen gene, β-galactosidase (β-gal). Growth of β-gal-positive Colon 26 tumors was retarded in the syngeneic mice immunized with β-gal and FasL DNA compared with those vaccinated with β-gal or FasL DNA. We did not detect increased numbers of β-gal-specific CD8+ T cells in lymph node of mice that received combination of β-gal and FasL DNA, but amounts of anti-β-gal antibody increased with the combination but not with β-gal or FasL DNA injection alone. Subtype analysis of anti-β-gal antibody produced by the combination of β-gal and FasL DNA or β-gal DNA injection showed that IgG2a amounts were greater in mice injected with both DNA than those with β-gal DNA alone, but IgG2b amounts were lower in both DNA-injected than β-gal DNA-injected mice. These data suggest that FasL is involved in boosting humoral immunity against a gene product encoded by coinjected DNA and enhances the vaccination effects.